If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -1(y + -1a) = -20 Reorder the terms: 4y + -1(-1a + y) = -20 4y + (-1a * -1 + y * -1) = -20 4y + (1a + -1y) = -20 Reorder the terms: 1a + 4y + -1y = -20 Combine like terms: 4y + -1y = 3y 1a + 3y = -20 Solving 1a + 3y = -20 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3y' to each side of the equation. 1a + 3y + -3y = -20 + -3y Combine like terms: 3y + -3y = 0 1a + 0 = -20 + -3y 1a = -20 + -3y Divide each side by '1'. a = -20 + -3y Simplifying a = -20 + -3y
| x^2-8x+16=15.625 | | 11x^2+11x-15=0 | | 32-20u=-2u-4 | | p-5(2-3p)= | | -10=5(a-1)-3a+1 | | 1-g+5-2g+3G-6= | | 4x+n=8 | | 2n-102=8 | | 5(2z-7)=6z+17+4z | | 12x-32= | | 5x+x=2.4 | | 5(8-4x)=80 | | 2.5-h=h/2 | | 543-654g=69 | | -12=x-10 | | 10-2p=p-14 | | .2x=7-x | | 0=2(v+4) | | 95=5s | | 8(q+1)+3q=-14 | | 9x-5(x-3)=5x | | 2a-22=18 | | 6x-5+8w-2w=9w-24 | | 6y-2=3y+13 | | G(x+5)=(x+5)+2(x+5)+3 | | 11p=77 | | (-4X-6)(X-5)=0 | | 3(19-9)+5=35 | | 3640=x(1+0.05*6) | | -2r^2-10r-12=0 | | 3n+46=1+n | | 7-3r=28 |